The Emergence of Environmental Flow Protection in Québec Law - Tremblay, Hugo (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2010)
The allocation of minimal quantities of water for environmental and biotic uses makes it possible to maintain healthy ecosystems and reinforces their ability to support human activities. The finite character of water resources, the increase in hydrologic variability owing to climatic changes, and the continuous augmentation of anthropomorphic water uses tend to reduce water quantities available for ecosystem usage. In this context, the legal protection of environmental flows acquires increasing importance. The following paper first proposes an overview of hydrologic principles that militate in favour of reserved instream flows. Then follows a brief review of legal provisions in various foreign jurisdictions describing the methods used for residual flows protection. In closing, an overview of the Québec legal framework for managing hydraulic resources determines the extent of legal protection afforded to environmental and biotic usages.